The effect of government policy on the relationship between organizational factors and construction waste management in Abuja, Nigeria - Nasidi, Yusuf (2016)
Poor motivation for the implementation of the construction on-site waste reduction, insufficient waste management skills, the shortage of appropriately designed and decently handled landfill system, lack of team work, unequal workload and task distribution among the divisions is the result of poor organizational structure among construction organizations in Nigeria. Lack of frequent staff training, performance management and human resource management practices and the problems of waste management regulations is the result of improper enforcement of waste management policy and planning framework for waste management. Further the inadequacy of unified waste management regulations and operational system for the enforcement and control of construction waste management practices among others are accountable for the unsuccessful construction waste management. Drawing upon the resource base view theory, this study aimed to examine the effects of government policy on the relationship between organizational factors and construction waste management. A stratified simple random sampling was adopted for the four categories of construction organizations that are registered with the Corporate Affairs Commission. Out of 331 questionnaires’ distributed to the construction organizations a total of 178 completed and valid questionnaires were returned, yielding a 53.7 percent response rate. Structural equation model, smart PLS algorithms and bootstrapping were adopted to achieve all of the research objectives. This study found out that organizational structure has a strong and positive relationship with construction waste management. Organizational resources established a strong and positive relationship with construction waste management among Nigerian construction organizations. The government policy shows a strong, positive relationship with construction waste management among construction organizations and it also moderates and strengthens the relationship positively between organizational structure and construction waste management in Abuja. Finally, the study further found that government policy also moderates the relationship between organizational resources and construction waste management in Abuja. The results support the hypothesized direct relationship of the organizational structure and construction waste management with the t-value of 7.09, organizational resources and construction waste management with the t-value of 10.16, government policy and construction waste management with the t-value of 5.42. Government policy moderates the relationship between organizational structure and construction waste management with the t-value of 2.61 and also it moderates the relationship between organizational resources and construction waste management with the t-value of 1.66. The study provides appropriate theoretical, practical contributions to the academic, industry and the policy-makers. It is therefore recommended that construction organizations should focus on organizational factors that influence construction waste management. This study focused on non-hazardous material waste. The study suggested that hazardous waste, time and overrun waste should also be considered; while case study or qualitative method could be adopted in future research.